Translanguaging as leverage for developing inclusive communication in superdiversity contexts of inner-city schools - Omidire, Margaret Funke (University of Pretoria, 2025)
Thesis (PhD (Learning Support Guidance and Counselling))--University of Pretoria, 2024.